Does the Earth Care? Indifference, Providence, and Provisional Ecology - Smith, Mick (University of Minnesota Press, 2022)
Rethinking our relationship with Earth in a time of environmental emergency The world is changing. Progress no longer has a future but any earlier sense of Earth as "providential" seems of merely historical interest. The apparent absence of Earthly solicitude is a symptom and consequence of these successive Western modes of engagement with the Earth, now exemplified in global capitalism. Within these constructs, Earth can only appear as constitutively indifferent to the fate of all its inhabitants. The "provisional ecology" outlined in Does the Earth Care?-drawing on a variety of literary and philosophical sources from Richard Jefferies and Robert Macfarlane to Martin Heidegger and Gaia theory-fundamentally challenges that assumption, while offering an Earthly alternative to either cold realism or alienated despair in the face of impending ecological disaster. Forerunners is a thought-in-process series of breakthrough digital works. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship.